Cooperative effect of chalcopyrite and bornite interactions during bioleaching by mixed moderately thermophilic culture. (September 2016) - Wang, Jun; Tao, Lang; Zhao, Hongbo; Hu, Minghao; Zheng, Xihua; Peng, Hong; Gan, Xiaowen; Xiao, Wei; Cao, Pan; Qin, Wenqin; Qiu, Guanzhou; Wang, Dianzuo
Highlights: Cooperative effect existed between chalcopyrite and bornite in bioleaching. Potential of 370–450 mV (vs. Ag/AgCl) is beneficial to chalcopyrite bioleaching. Galvanic current and appropriate redox potential promote chalcopyrite bioleaching. Abstract: The cooperative interactions between chalcopyrite and bornite during bioleaching by mixed moderately thermophilic culture were investigated mainly by bioleaching experiments and electrochemical experiments. Bioleaching results showed that a cooperative effect existed between chalcopyrite and bornite. When the mass ratio of chalcopyrite to bornite was 3:1, an extremely high copper extraction of more than 88% was achieved after bioleaching for 27 days. One of the major reasons for the cooperative effect was that a certain redox potential range (370–450 mV vs. Ag/AgCl) could be maintained for a long period of time during bioleaching due to the mixture of chalcopyrite and bornite. Electrochemical measurements revealed that chalcopyrite was much easier to be reduced than oxidized, while bornite was prone to be directly oxidized. Hence, galvanic effect between chalcopyrite and bornite enhanced the reduction of chalcopyrite to secondary copper-iron species and promoted the oxidative dissolution of bornite. Therefore, redox potential controlling and galvanic effect both contributed to the cooperative bioleaching of chalcopyrite and bornite.